“Moon Phrases”: A Social Media Facilitated Tool for Emotional Reflection and Wellness - De Choudhury, Munmun; Gamon, Michael; Hoff, Aaron; Roseway, Asta (European Alliance for Innovation, 2013)
We propose an early prototype: a web-based tool “Moon Phrases” that leverages an individual’s social activity online for promoting emotional reflection and wellness. Specifically, Moon Phrases tracks the emotion and linguistic expression of individuals as manifested on the social media Twitter, and presents a novel visualization—an analogy to the phases of the moon, to reveal their longitudinal trends. Social media platforms, including Twitter and Facebook provide a window onto the thoughts and feelings of individuals around small and big happenings in their lives. Motivated from research in psychology and HCI, we hypothesize that identifying the changes in language, emotion, and social activity on social media would enable individuals to reflect on their own behavior over time and in a fine-grained manner, which are otherwise known to be difficult to keep track of. We believe Moon Phrases thus bears the potential to act as a self-narrative or “behavioral fingerprint”, and thereby serve as an unobtrusive mechanism to facilitate emotional wellness in individuals.